PEMANFAATAN USAHA PLASTIK KELEMAN DALAM UPAYA PENINGKATAN PENGHASILAN IBU-IBU DI DESA GLAGAHWERO KECAMATAN KALISAT KABUPATEN JEMBER JAWA TIMUR - Roro Aditya Novi Wardhani (LPPM Universitas PGRI Argopuro Jember, 2018)
This socialization activity is a program to invite women to participate in helping the business by joining filling dirty plastic received from collectors. The existence of plastics plastics business can participate empower women in the district Kalisat, have income that helps the husband's income. Mothers can take the time to help with the plastic plastics business by helping to clean the plastic that has been collected. Increased income in the family not only allows for husband, wife can also help. Increase family costs.